Integrated termite management in degraded crop land in Diga district, Ethiopia - Legesse, H.; Taye, H.; Geleta, N.; Swaans, Cornelis P.M.; Fikadu, D.; Zziwa, Emmanuel; Peden, Donald G. (International Livestock Research Institute, 2013)
Termites are a major pest in the semi-arid and sub-humid tropics. They pose a serious threat to agricultural crops, forestry seedlings, rangelands and wooden structures. In Ethiopia the problem is particularly serious in the western part of the country, specifically in Wollega Zones of Oromia Region. In the past, several attempts were made to reduce damage caused by termites, including extensive termite mound poisoning campaigns. These interventions not only had a negative effect on the environment, but were also largely ineffective. Based on previous work in Uganda showing that adding organic matter to the soil diverts termites from the plant and functions as alternative feed source, a project was commenced by the Challenge Program for Water and Food (CPWF). In partnership with IWMI and Makerere University, ILRI and Wollega University took the lead in working with local stakeholders to identify sustainable solutions to address the termite problem in Diga, Ethiopia. The research consisted of two major activities; 1) a baseline study to better understand the relation between land use, water, termites and local institutions; and 2) the design and testing of identified interventions. The baseline findings indicated that termite damage depends on various biophysical and socio-institutional factors, which requires an integrated, but also targeted, termite management approach; two termite species are locally recognized, but level of knowledge highly varies among farmers within and between kebeles. Various trials were designed for on-farm experimentation using cattle manure and crop residues as alternative feed source for termites in combination with other cultivation techniques. The result obtained indicated that application of cattle manure and crop residues increases the organic matter content of the soil by 24.5 and 13.9%—grain yield of maize by 38.8 and 16.7% and reduces termite count per plant by 29.6 and 21.6% as compared to the control treatment, respectively. The results are in line with farmers’ own evaluation of the trials. Results and implications are discussed.